(untitled) (Revista Direitos Humanos e Democracia, 2024)
Immersed in the context of the accelerated, concentrated and disorderly process of Brazilian urbanization, this article deals with the challenges of realizing the fundamental human right to housing based on an analysis that has a double objective. First, it is proposed to carry out an examination of the role of the Brazilian State and its characteristics regarding the provision of public services of general interest and socialization of the State from a perspective that considers the transition or passage from a liberal State to a social and democratic law and its implications regarding the right to property and, above all, the right to housing. Second, analyze whether, and how, the Brazilian State would be ensuring the right to housing through the recognition and affirmation of this right in the Brazilian constitutional order. Methodologically, the work makes use of bibliographic and documentary research. As a result, the data analyzed suggest that there have been considerable advances in terms of recognizing and affirming the fundamental right to housing in Brazilian constitutional law, especially based on the principles of human dignity and the social function of property, as well as in the ratification of international treaties and conventions. .It is concluded that these advances were only possible through the promulgation of the 1988 citizen constitution and subsequent constitutional amendments and the disruptive and innovative urban policy instruments brought within the City Statute. The federal constitution and the city statute stand as important and effective legal norms imposed by the State in order to implement the fundamental human right to housing.